Transcriptional time-course analysis during ash dieback infection revealed different responses in tolerant and susceptible Fraxinus excelsior genotypes - Víctor Chano; Renata Callegari Ferrari; Tania Domínguez-Flores; Karuna Shrestha; Barbara Fussi; Hannes Seidel; Oliver Gailing; Katharina B. Budde (BMC Plant Biology)
Abstract Hymenoscyphus fraxineus, the causal agent of Ash Dieback (ADB), has been introduced to eastern Europe in the 1990s from where it spread causing decline in European ash populations. However, the genetic basis of the molecular response in tolerant and susceptible ash trees to this disease is still largely unknown. We performed RNA-sequencing to study the transcriptomic response to the disease in four ash genotypes (ADB-tolerant FAR3 and FS36, and ADB-susceptible UW1 and UW2), during a time-course of 7, 14, 21, and 28 days post-inoculation, including mock-inoculated trees as control samples for each sampling time point. The analysis yielded 395 and 500 Differentially Expressed Genes (DEGs) along the response for ADB-tolerant FAR3 and FS36, respectively, while ADB-susceptible UW1 and UW2 revealed 194 and 571 DEGs, respectively, with most DEGs found exclusively in just one of the genotypes. DEGs shared between tolerant genotypes FAR3 and FS36, included genes involved in the production of phytoalexins and other secondary metabolites with roles in plant defense. Moreover, we identified an earlier expression of genes involved in both pattern- and effector-triggered immunity (PTI and ETI) in ADB-tolerant genotypes, while in ADB-susceptible genotypes both responses were delayed (late response). Overall, these results revealed different transcriptomic expression patterns not only between ADB-tolerant and ADB-susceptible genotypes, but also within these two groups. This hints to individual responses in the natural tolerance to ADB, possibly revealing diversified strategies across ash genotypes.